Greenhouse gas emissions from high-speed rail maintenance: A comparative case study for five major high-speed lines - Rafael Damián; Clara I. Zamorano (Sustainable Futures)
While high-speed rail is recognized for its environmental benefits during the operational stage, maintenance activities present significant yet often overlooked sources of emissions. This study provides a general evaluation of the greenhouse gas emissions associated with the maintenance of high-speed rail infrastructure across five high-speed lines in countries with extensive networks: China, Spain, Japan, France and Germany, in four maintenance dimensions: equipment manufacturing, equipment operation, maintenance facilities operation and staff commuting.Our findings reveal that these activities collectively make a substantial contribution to the overall carbon footprint of high-speed rail systems, generating emissions with an order of magnitude of tens to hundreds of tonnes of carbon dioxide equivalent per hundred kilometres of double track per year. We also found significant differences in the amount and distribution of these maintenance emissions between the high-speed lines studied, mainly due to country-specific differences such as their energy mix or car fleet technology, or variations between the railway administrators’ maintenance plans, such as different maintenance schedules or the configuration of the facilities.Based on this analysis, we have also identified specific targeted recommendations and potential mitigation strategies that may help to reduce high-speed rail maintenance emissions in the field of robotization, electrification or the workers’ transport routines. These are deemed useful for fulfilling the different pledges made by these countries to drastically cut emissions but must be considered in a holistic manner with other railway lifecycle stages such as construction and operation, as there may be important connections and trade-offs.